Essence Apparatus - Schrattenholz, Maria Dorothea (School of Languages and Literatures, 2022)
Essence Apparatus is a collection of fiction short stories rooted in poetry and the traditions of ‘the uncanny' and ‘weird' writing. Included are also three expository essays relating to my creative work and its contextual and theoretical underpinnings, going in-depth on my relationship with the genre of science fiction and its literary device ‘cognitive estrangement', the tradition of writing the uncanny and the weird, and my Scandinavian and South African sources of inspiration. The short story collection Essence Apparatus feature zombies in Finland; an animalistic metamorphosis on the archipelago of Svalbard; the Chernobyl accident; humans living on Mars returning to their origins on Earth, but also interpersonal relationships between a daughter and her father, two sisters, and lovers. The stories explore the hard problem of consciousness and other philosophical questions; the search for knowledge and a feeling of belonging in a nature not fully understood, and the mechanisms of translocation and transfiguration as a fundamental part of being human.